ANALISIS FAKTOR YANG MEMPENGARUHI KEMISKINAN DI PROVINSI BENGKULU - Helmy Haliansah (2022)
Poverty is one of the thorny problems for various countries, especially developing countries. The right methods and policies are needed in order to reduce the poverty rate in each country so that public welfare can be achieved. The purpose of this study is to determine the effect of population, education level, government expenditure and human development index on poverty in Bengkulu Province. This study took samples using saturated sampling techniques in 10 regencies/cities within a period of 5 years, namely 2017-2021, then the samples contained in this study were 50 data whose sources were obtained from the Central Statistics Agency (BPS) and the Directorate General of Financial Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia. This study used panel data regression analysis through E-views 10 as a data processing instrument. The results of the study stated that partially the population and government expenditure did not show a significant influence on the poverty rate, while the level of education and HDI showed a significant influence on poverty. Simultaneously, the results of this study show that the population, level of education, government expenditure and HDI affect poverty.